Sensory Integration during Vibration of Postural Muscle Tendons When Pointing to a Memorized Target - Teasdale, Normand; Furmanek, Mariusz P.; Germain Robitaille, Mathieu; de Oliveira, Fabio Carlos Lucas; Simoneau, Martin (Frontiers in Human Neuroscience, 2017)
Vibrating ankle muscles in freely standing persons elicits a spatially oriented postural response. For instance, vibrating the Achilles tendons induces a backward displacement of the body while vibrating the tibialis anterior muscle tendons induces a forward displacement. These displacements have been called vibration induced falling (VIF) responses and they presumably are automatic. Because of the long delay between the onset of the vibration and the onset of the VIF (about 700 ms), and the widespread cortical activation following vibration, there is a possibility that the sensory signals available before the VIF can be used by the central nervous system to plan a hand pointing action. This study examined this suggestion. Ten healthy young participants stood on a force platform and initially were trained to point with and without vision to a target located in front of them. Then, they were exposed to conditions with vibration of the Achilles tendons or tibialis anterior muscle tendons and pointed at the target without vision. Vibration stopped between each trial. Trials with vision (without vibration) were given every five trials to maintain an accurate perception of the target’s spatial location. Ankle vibrations did not have an effect on the position of the center of foot pressure before the onset of the pointing actions. Furthermore, reaction and movement times of the pointing actions were unaffected by the vibration. The hypotheses were that if proprioceptive information evoked by ankle vibrations alters the planning of a pointing action, the amplitude of the movement should scale according to the muscle tendons that are vibrated. For Achilles tendon vibration, participants undershot the target indicating the planning of the pointing action was influenced by the vibration-evoked proprioceptive information (forward displacement of the body). When the tibialis anterior were vibrated (backward displacement of the body), however, shorter movements were also observed. Longer movements (that were expected) would have increased the backward response of the sensed body movement. Thus, it is possible that pointing actions were adjusted on the basis of the expected consequences of the planned pointing action to avoid a response that could have compromised postural stability.